THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON STUDENTS' LEARNING INTEREST IN QUADRATIC FUNCTION MATERIAL FOR CLASS X - Silitonga, Romayana Gloria; Sauduran, Golda Novatrasio; Panjaitan, Simon M. (Dharmas Education Journal (DE_Journal), 2023)
Study This aim For know the influence of the Problem-Based Learning (PBL) model on interest Study students in the eye lesson function square. The type of research used is study quantitative with approach experiment. Population study is all over student class X of State Senior High School 14 Medan, with sample as many as 36 students. The instruments used researchers is questionnaire interest learning and observation study. Research results show existence significant influence of the PBL learning model on interest Study students. Based on analysis regression simple obtained equality regression Ŷ = 6.265 + 1.180X, with t - value of 33.616 and the t table value amounting to 2,032. This is show existence positive and significant relationship between variables free (PBL model) with variables bound ( interest Study students ). More further, significance test regression show that calculated F value more than 1130 big than F table value of 4.13 at the level significance of 5%. This is show that the regression model the in accordance For predict interest Study students. Coefficient determination (R²) of 0.971 indicates that 97.1% of the variation in interest Study student can explained by the application of the PBL learning model. With thus, it can concluded that the PBL model has very large and significant influence to improvement interest Study students in the eye lesson function square.